Comparing Exceptionalism in France and the USA - Elsa Devienne (European Journal of American Studies)
This article challenges the current scholarship on the history of the death penalty and its abolition by adopting a transatlantic framework and debunking the popular contemporary conception of the “Barbaric Americans” against the “civilised” anti-death penalty French. The article focuses on the short period in the 1970s during which American executions were halted by the Supreme Court, while France was still putting prisoners to death in cases that were widely debated in public opinion. By observing the French media’s reactions to the two major decisions taken by the Supreme Court in the 1970s and their direct consequences, this essay analyzes not only the French gaze on American practices but also how these American decisions were manipulated by the journalists to stoke the French debate about abolition.